Systemic Therapy in Men With Metastatic Castration-Resistant Prostate Cancer: American Society of Clinical Oncology and Cancer Care Ontario Clinical Practice Guideline - Basch, Ethan (J Clin Oncol, 2014)
PURPOSE: To provide treatment recommendations for men with metastatic castration-resistant prostate cancer (CRPC). METHODS: The American Society of Clinical Oncology and Cancer Care Ontario convened an expert panel to develop evidence-based recommendations informed by a systematic review of the literature. RESULTS: When added to androgen deprivation, therapies demonstrating improved survival, improved quality of life (QOL), and favorable benefit-harm balance include abiraterone acetate/prednisone, enzalutamide, and radium-223 ((223)Ra; for men with predominantly bone metastases). Improved survival and QOL with moderate toxicity risk are associated with docetaxel/prednisone. For asymptomatic/minimally symptomatic men, improved survival with unclear QOL impact and low toxicity are associated with sipuleucel-T. For men who previously received docetaxel, improved survival, unclear QOL impact, and moderate to high toxicity risk are associated with cabazitaxel/prednisone. Modest QOL benefit (without survival benefit) and high toxicity risk are associated with mitoxantrone/prednisone after docetaxel. No benefit and excess toxicity are observed with bevacizumab, estramustine, and sunitinib. RECOMMENDATIONS: Continue androgen deprivation (pharmaceutical or surgical) indefinitely. Abiraterone acetate/prednisone, enzalutamide, or (223)Ra should be offered; docetaxel/prednisone should also be offered, accompanied by discussion of toxicity risk. Sipuleucel-T may be offered to asymptomatic/minimally symptomatic men. For men who have experienced progression with docetaxel, cabazitaxel may be offered, accompanied by discussion of toxicity risk. Mitoxantrone may be offered, accompanied by discussion of limited clinical benefit and toxicity risk. Ketoconazole or antiandrogens (eg, bicalutamide, flutamide, nilutamide) may be offered, accompanied by discussion of limited known clinical benefit. Bevacizumab, estramustine, and sunitinib should not be offered. There is insufficient evidence to evaluate optimal sequences or combinations of therapies. Palliative care should be offered to all patients.